Effect of bovine lactoferrin and lactoferrin-derived peptides on planktonic cells and abiotic surface biofilms of Salmonella enterica - Angulo-Zamudio, Uriel A; Canizalez-Roman, Adrian; Flores-Villaseñor, Hector; Bolscher, Jan G M; Nazmi, Kamran; Leon-Sicairos, Claudia; Acosta-Smith, Erika; Quintero-Martínez, Laura E; León-Sicairos, Nidia (Journal of dairy research, 2025)
is a Gram-negative bacterium responsible approximately for 155,000 deaths annually. is one of the most important foodborne pathogens, affecting mainly people in developed countries. The human immune system produces antibacterial peptides and proteins like lactoferrin (LF). This work addresses the hypothesis that bovine lactoferrin (bLF) and its derivative peptides bLactoferricin17-30, bD-Lactoferricin17-30, bLactoferrampin265-284, bD-Lactoferrampin265-284 and bLF-chimera have antimicrobial activity on planktonic cells and pre-formed biofilms of . Planktonic ATCC 14028 were treated with bLF and bLF-peptides for two hours, and bacterial viability was determined by counting colony-forming units/ml. In addition, biofilms were pre-formed or established on an abiotic surface, and viability or disruption was assessed in the presence of bLF and bLF-peptides by counting colony-forming units/ml or using the live/dead viability kit. We observed that bLF and bLF-peptides were bactericidal against planktonic , killing more than 80% of cultures after two hours of treatment. The bactericidal effect was concentration and time-dependent. In addition, bLF, bLFampin165-284, and bLF-chimera showed an anti-biofilm effect against biofilms pre-formed during 8 and 12 hours on the abiotic surface, disorganizing more than 50% of the biofilms after 4 or 6 hours of treatment. We conclude that bLF and its peptides show antimicrobial activity against planktonic cells and pre-formed biofilms of on abiotic surfaces and could potentially be a therapeutic solution to combat infections.